Study on drug use pattern in primary health care centers of Kathmadu Valley. - Aryal,Amrita (2019)
ABSTRACT: Background: Drug use evaluation is a systematic and criteria-based drug evaluation, which ensures the appropriate drug use. The purpose of this study was to analyze drug use situation in Primary health care centers of Kathmandu valley by following WHO drug use indicators namely; prescribing indicators, patient care indicators and health facility indicators. Methodology: A cross sectional descriptive study was performed in all Primary healthcare centers of Kathmandu valley. A total 600 prescriptions were analyzed retrospectively choosing Simple random sampling method from recent month of prescriptions for prescribing indicators. 120 patients were encounter for patient care indicator and health facility representatives were interviewed for health facility indicator. The data was collected analyzed by following the WHO drug use indicator guidelines and shown pictorially using MS- Excel 2013 Result: The study showed that average number of drugs per encounters was found to be 2.6. Most commonly prescribed drugs were found to be Acetaminophen, Ranitidine and Amoxicillin. Percentage of drugs prescribed by generic name was found to be 59.97%. Encounters with an antibiotics and injection prescribed were found to be 58 % and 4.17% respectively. Percentage of drugs prescribed from EDL was found to be 80.89%. Average consultation and dispensing time was found to be 3.6 min and 54.36 sec respectively. The percentage of drugs actually dispensed was found to be 76.57%. The patient's knowledge on correct dose was found to be only 50% and no drugs were adequately labeled. The majority of dispensers involved were Intern Nursing Students (42%) and all prescribers were medical officers. Out of 12 PHCs, 10 of them had copy of EDL. The availability of drugs in PHCs was found to be only 64.65%. Conclusion: The observed values for all INRUD indicators were deviated from the established norms. Patient care provided by health facilities studied was insufficient and thus effective intervention program for promotion of rational drug use practice is recommended in PHCs. Keyword: Drug use pattern, Prescribing indicator, Patient care indicator, Health facility indicator